Salmonella Enteritidis ST11 Prosthetic Valve Endocarditis Complicated by a Paravalvular Abscess: Case Report and Literature Review - Shiori Kitaya; Shintaro Katahira; Hiroaki Baba; Yoshikatsu Saiki; Yukio Katori; Koichi Tokuda; Hajime Kanamori (Applied Microbiology, 2023)
Salmonella infection typically causes self-limiting gastroenteritis. However, in rare cases, it can lead to prosthetic valve endocarditis (PVE), especially in older adults with a history of valve replacement surgery. In this case study, we describe a case of Salmonella PVE in a man with a prosthetic aortic valve. Complications of PVE include abscess formation, which is associated with increased mortality. If a patient with a history of prosthetic valve replacement presents with symptoms suggestive of gastroenteritis or bacteremia, a thorough investigation should be conducted with suspicion of PVE. The prognosis of Salmonella PVE can be improved by promptly initiating appropriate antibiotics and administering them for an adequate duration, as well as by considering surgical intervention when necessary. Additionally, confirming negative blood cultures after treatment of Salmonella bacteremia is important to prevent the development of PVE and paravalvular abscesses.